Mixotrophic cultivation of microalgae to enhance the biomass and lipid production with synergistic effect of red light and phytohormone IAA. (March 2022) - Chang, Wenjuan; Li, Yanpeng; Qu, Yanhui; Liu, Yi; Zhang, Gaoshan; Zhao, Yan; Liu, Siyu
Abstract: Microalgal cultivation still presents a big challenge in commercial application due to the small size and low density of microalgae. The effect of phytohormones or light spectra on enhancing microalgal growth has been individually demonstrated at the bench scale. However, the synergistic action of phytohormones and light spectra on algal growth and lipid production remains unclear. In this study, the optimal carbon and nitrogen concentrations, as well as the optimum dosage of the phytohormone indole-3-acetic acid (IAA), for the growth of Chlorella vulgaris were first evaluated under mixotrophic cultivation. A light spectrum experiment was then conducted in an incubator equipped with white and red light. Results show that optimal mixotrophic cultivation conditions were 10 g L −1 glucose, 2250 mg L −1 sodium nitrate and 10 mg L −1 IAA. Under the optimum IAA treatment and irradiation with red light, the highest biomass, lipid content and lipid productivity were 28.34%, 3.53 g L −1 and 140.04 mg L −1  d −1, respectively. As compared to white light, the synergistic action of red light and IAA stimulated biomass production and lipid accumulation by algal cell metabolism and carbon source bioconversion. Furthermore, the post-optimized C. vulgaris had the potential for biodiesel production. These results provide new insights for the highly efficient cultivation of microalgae. Graphical abstract: Image 1 Highlights: C & N sources were tested to optimize the conditions for mixotrophic cultivation. IAA increased biomass production by 11% and lipid yield by 16%, versus no IAA. Red light promoted the increase of biomass under optimal C & N source conditions. Synergy of IAA and red light greatly enhanced algal biomass and lipid accumulation.